Inserção da educação ambiental no currículo escolar: estratégias pedagógicas e práticas para a vida - Tavares, Aline Rebecca Cordeiro Fonseca (2024)
Environmental issues make up the repertoire of emerging themes linked to the current crisis of civilization, revealed by socio-environmental imbalances in the face of man-made transformations of the natural environment. School education, the disseminator of human knowledge and a space for the construction of science, confronts the need to discuss the relationship between society and nature, bringing environmental issues that deserve to be highlighted into the basic education curriculum, in conjunction with students' contexts. The aim of the study was to include Environmental Education in the school curriculum, integrated into the Formative Itineraries by means of an Elective Curricular Unit, working on environmental issues in secondary education, entitled Environmental Education as a Practice for Life. This is a qualitative-quantitative study whose methodological strategies involved: bibliographical, exploratory and participant research, developed with students in a basic education school in the city of Natal/RN. The activities were mediated by active methodologies, based on thematic workshops, an inverted classroom, field studies and the problematization methodology, with contextualized studies to address ecological concepts and contemporary environmental issues, with a view to building an elective curricular unit for secondary education. The data was obtained by analyzing official documents, applying questionnaires, participant observation, various records and focus groups. The themes raised, the perceptions and understandings expressed by the students and the analysis of the current curriculum structure supported the development of the elective curriculum unit. The structuring axes of this development involve teaching by investigation and life projects. The participatory processes involved in the construction and implementation of the curricular unit contributed to the students' comprehensive education in terms of environmental awareness and the exercise of citizenship, revealed by the attitudes expressed, such as: recognition of initial limitations, interest in the subject in class and the search for viable alternatives to environmental problems. Topics such as: water pollution, heat islands, soil and air pollution, sewage dumping, inappropriate waste disposal, the global climate crisis, adaptations and precautions to tragic events and the urgent need to change paradigms about our relationship with the environment were addressed. The students came up with questions, pointed out important points and theorized in order to build arguments to explain scenarios from their reality. The experience of the research is systematized in a "Portfolio on the Implementation of Environmental Education in the New Potiguar High School", as a didactic-pedagogical tool to support basic education teachers in the insertion of environmental education in the school space, presenting the path, methodology and knowledge produced in the activities.